Broad-Spectrum Suppression of Innate Immunity Is Required for Colonization of Arabidopsis Roots by the Fungus Piriformospora indica(1)([C])([W]) - Jacobs, Sophie (American Society of Plant Biologists, 2011)
Piriformospora indica is a root-colonizing basidiomycete that confers a wide range of beneficial traits to its host. The fungus shows a biotrophic growth phase in Arabidopsis (Arabidopsis thaliana) roots followed by a cell death-associated colonization phase, a colonization strategy that, to our knowledge, has not yet been reported for this plant. P. indica has evolved an extraordinary capacity for plant root colonization. Its broad host spectrum encompasses gymnosperms and monocotyledonous as well as dicotyledonous angiosperms, which suggests that it has an effective mechanism(s) for bypassing or suppressing host immunity. The results of our work argue that P. indica is confronted with a functional root immune system. Moreover, the fungus does not evade detection but rather suppresses immunity triggered by various microbe-associated molecular patterns. This ability to suppress host immunity is compromised in the jasmonate mutants jasmonate insensitive1-1 and jasmonate resistant1-1. A quintuple-DELLA mutant displaying constitutive gibberellin (GA) responses and the GA biosynthesis mutant ga1-6 (for GA requiring 1) showed higher and lower degrees of colonization, respectively, in the cell death-associated stage, suggesting that P. indica recruits GA signaling to help establish proapoptotic root cell colonization. Our study demonstrates that mutualists, like pathogens, are confronted with an effective innate immune system in roots and that colonization success essentially depends on the evolution of strategies for immunosuppression.